Risk of flood to the light of global climate change in Northeastern Argentina - Popolizio, Eliseo (Journal of Nepal Geological Society, 2000)
During the 20th century, several catastrophic pluvial and fluvial floods took place over the northeastern region of Argentina. These disastrous floods caused great damage worth hundreds of millions of US dollars. The rehabilitation programme was supported by regional economies. The idea of this paper is to point out the risks of greater floods as a consequence of the global climatic change. The experiences obtained from the palaeogeomorphological research, historical data over the regional rivers, and the climatic and environmental changes are taken into account in this research. The record of the geomorphological study of the region strongly suggests that in past epochs, different wet and dry periods occurred with the global climate change, especially in the Quaternary Period. It is possible to infer that the region is very sensitive to these changes and anthropogenic action. On the other hand, environmental and climatic conditions show a tendency of tropicalising the area. In this case, consequences are unpredictable if the processes are evolving rapidly. It is possible to observe that after the 1960's, the characteristics of the fluvial courses are changing. The changes are in the direction of the maximum and minimum amplitudes with the same mean values. Besides, the frequency of large floods has increased from the 1960’s. The Parana River, the largest fluvial course of the region, serves as a model for the propositions mentioned above. This is because we have historical records from 1748 on high flood levels and hydrometrical measurements from 1900. The northeastern region is a very vast and flat plain with an inefficient drainage system. This physical framework induces pluvial flooding, which covers millions of hectares. True catastrophes develop when pluvial and fluvial floods coincide. The record of overflows has a recurrence period of less than 50 years. This strongly suggests a very high risk. In the 21st century, it is very probable that flooding phenomena greater than known will occur. But no mitigation measures are planned to face them.